Effects of Natural compound “Piperine” on the growth and Adhesive Properties of Streptoccus Mutans Bacterial Biofilm - Habib, Tasnia; Parvin, Farhana (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: “Streptococcus mutans” bacterial biofilm is known to be a major causative organism for dental plaque which is acknowledged to be associated with biofilm. In this study we aim to evaluate the effectiveness of natural compound “Piperine” on the biofilm of “Streptococcus mutans” bacteria from One hundred cases of Dental unit Of Rajshahi Medical College. Methods: This longitudinal study was conducted in the Molecular Pathology with the Insect Biotechnology Lab, IBSc of Rajshahi University and Dental Unit of Rajshahi Medical College from October 2017 to October 2019. A total of 100 cases were selected for this study from the same institution, collected dental plaque sample, identified, and isolated Streptococcus mutans bacteria by using MSB Agar (Mitis salivarius-bacitracin) medium, formation and detection of “Streptococcus mutans” bacterial biofilm using a Microtiter plate biofilm assay method. Then we collected Medicinal plant “Black pepper” from a standard medical food supply, extracted, isolated, purified and identified a specific compound named as “Piperine” by using Column chromatographic and Nuclear magnetic resonance spectroscopic (NMR) techniques and analysis their antimicrobial effectivities. Result: Our Result demonstrated that “Streptococcus mutans” bacterial biofilm represents a very strong microbial attachment with the tooth surface and after the application of 100ul ethyl acetate extract of piperine showed 77% growth of reduction with the value of P<0.001 in case of patient no 17, 75% growth inhibition with the value of P <0.003 in case of patients no 55 and 77% growth of inhibition with the value of p<0.005 in case of patients no 95 against the biofilm of streptococcus mutans bacteria. Conclusion:After some investigations it was revealed the ethyl acetate extract of compound “Piperine” showed the highest antibiofilm activities. J Bangladesh Coll Phys Surg 2023; 41: 33-39